Evaluating government training programs for the economically disadvantaged - Friedlander, Daniel [Verfasser]; Greenberg, David H. [Verfasser]; Robins, Philip K. [Verfasser] (My University, 1997)
"Evaluations of the effectiveness of government training programs for the economically disadvantaged have been accumulating for more than three decades. Additionally, in the past decade, a rapidly expanding literature has focused on the methodology of training program ecaluation. The time is ripe for collectling and interpreting the empirical findings from this literature and for assessing the status of evaluation methodology. The broadest generelization about the current knowledge of government training programs for the disadvantaged is that they have produced modest positive effects on employment and earnings for adult men and women that are roughly commensurate with the modest amounts of resources expended on them. The positive effects for adults are not large enough to produce major aggregate effects on employment and earnings among low-income target groups, and the programs have not made substatial inroads in reducing poverty, income inequality, or welfare use. Moreover, they have failed to produce positive effects for youth. In this article, we investigate the methodological foundations and empirical support for this view, suggest possible modifications of it, and identify potentially fruitful areas for future research by economists." (author-s abstract, IAB-Doku) ((en)) Literaturbericht zu Evaluationsstudien über Weiterbildungsprogramme für Benachteiligte in der USA und ihre Wohlfahrts- und Beschäftigungseffekte. (IAB)
Keywords: L 6.2.3 Evaluation; G 1.2 Arbeitsmarkt; S 2.3 Berufsbildungspolitik; I 2.3.2 Nordamerika; Literaturbericht; Wirkungsforschung; Berufliche Weiterbildung; Arbeitsmarktpolitik; Programm; Beschäftigungseffekte; Quantitative Angaben; USA